Moorean Absurdities and the Nature of Assertion - WILLIAMS, John N. (Institutional Knowledge at Singapore Management University, 1996)
I argue that Moore's propositions, for example, 'I went to the pictures last Tuesday but I don't believe that I did' cannot be rationally believed. Their assertors either cannot be rationally believed or cannot be believed to be rational. This analysis is extended to Moorean propositions such as God knows that I am an atheist and I believe that this proposition is false. I then defend the following definition of assertion: anyone asserts that p iff that person expresses a belief that p with the intention of causing relevant epistemic change in the cognition of an actual or potential audience.